The prevalence and predictors of disordered eating in women with coeliac disease. (1st December 2016) - Satherley, Rose-Marie; Howard, Ruth; Higgs, Suzanne
Abstract: Purpose: The need for dietary management in coeliac disease may lead to the development of disordered eating. This study examined the prevalence of disordered eating and factors predicting disordered eating in women with coeliac disease, compared with other dietary-controlled conditions. Methods: A cross-sectional, online survey assessing psychological well-being, disordered eating behaviours (Eating Attitudes Test 26 (EAT-26); Binge Eating Scale (BES)) was distributed using online forums, to those with coeliac disease (N = 157), inflammatory bowel disease (N = 116), type two diabetes (N = 88) and healthy controls (N = 142). Hierarchical regressions were conducted to explore and compare the predictors of EAT-26 and BES scores across all groups. Within the coeliac disease group, a cluster analysis was conducted to examine types of disordered eating. Results: Higher EAT-26 scores were found in those with coeliac disease and inflammatory bowel disease compared with healthy controls and type two diabetes; participants with a chronic health condition had higher BES than healthy control participants. The factors associated with EAT-26 scores differed across the dietary-controlled health conditions, with dietary management being important for those with coeliac disease. Psychological distress was associated with binge-eating behaviour across all groups. Cluster analyses found two types of disordered eating in coeliac disease; a binge eating type and a restrictive type. Conclusions: Disordered eating attitudes and behaviours are more prevalent in participants with chronic health conditions relative to healthy controls. The presence of binge eating behaviours in coeliac disease may be related to non-coeliac disease specific factors such as the distress associated with dietary-controlled illness. EAT-26 scores in coeliac disease are associated with disease specific factors, unique to following the gluten-free diet. These factors are important for identifying and supporting those with coeliac disease and disordered eating.